Epileptic encephalopathy with features of rapid‐onset dystonia Parkinsonism and alternating hemiplegia of childhood: a novel combination phenotype associated with ATP1A3 mutation. Issue 1 (13th March 2020) - Tran, Linh; Richards, Jason; McDonald, Marie; McConkie‐Rosell, Allyn; Stong, Nicholas; Jasien, Joan; Shashi, Vandana; Mikati, Mohamad A.
ABSTRACT: Mutations in ATP1A3 have been found to cause rapid‐onset dystonia Parkinsonism, alternating hemiplegia of childhood, epileptic encephalopathy and other syndromes. We report a four‐year, nine‐month‐old boy with episodes of frequent and recurrent status epilepticus, who first began having generalized tonic‐clonic seizures at four months of age. Development was normal until the age of four months, and markedly slowed down after the onset of seizures. Between the age of seven months and two and a half years, the patient had recurrent attacks of unilateral and bilateral hemiplegia. At the age of 21 months, after a febrile illness with status epilepticus, he regressed and developed continuous severe dystonia and bradykinesia with superimposed intermittent painful dystonic spasms. Extensive neurological and genetic workup revealed a de novo p.V589F ATP1A3 mutation (NM_152296.5:c.1765G>T, NC_000019.9:g.42482344C>A). This is a novel mutation associated with a novel phenotype that shares features with epileptic encephalopathy, alternating hemiplegia of childhood, and rapid‐onset dystonia Parkinsonism.